Modeling snowflake divertors in MAST-U tokamak using UEDGE code. (March 2021) - Khrabry, A.I.; Soukhanovskii, V.A.; Rognlien, T.D.; Umansky, M.V.; Moulton, D.; Harrison, J.R.
Abstract: In a snowflake (SF) divertor, two magnetic field nulls are placed close to each other creating four strike points (SPs) cf. two in a standard single-null (SN) divertor. In preparation to MAST-U experiments, magnetic configurations with SN and SF divertors located symmetrically at the top and at the bottom of the tokamak were modeled using a two-dimensional multi-fluid code UEDGE with a full plasma transport model featuring charge-state-resolved sputtered carbon impurities. SF configurations with various relative locations of the nulls and small null separation were considered. The complex interplay of the plasma transport and magnetic configurations was comprehensively studied using a simple model for the theoretically predicted fast plasma mixing (the "churning" mode) in the two-null SF region. The modeling results show that: 1) SF-plus and SF-minus configurations with closely located nulls produce same plasma parameters and heat fluxes at same SPs; 2) SF divertors approach the outer and inner SP detachment conditions at lower upstream density w.r.t. SN divertor; 3) heat flux profiles at primary SPs are substantially broadened and peak values are reduced in SF configurations w.r.t. SN divertor; this effect becomes more pronounced with the fast plasma mixing increase; 4) with the SF mixing, secondary SPs receive up to 10% (each) of the heat flux to the primary outer SP.